Grænser for deltagelse - Bolt, Mikkel (K&K - Kultur og Klasse, 2014)
Through a focus on the discourse of participation and the rhetoric of New Institutionalism the article presents an analysis of the on-going transformation taking place within the art institution following the outbreak of the financial crisis in 2007-2008 where so-called progressive art institutions are exposing former hidden class alliances. One case in point being the exhibition “Abstract Possible” at Tensta Konsthall in Stockholm where Tensta Konsthall collaborated with the local auction house Bukowskis owned by Lundin Petroleum under investigation of committing humanitarian crimes in Sudan. The article is a contribution to the critical analysis of the financialization of contemporary art in a situation where creativity has become high currency.